Find a stranger, say goodbye - Lowry, Lois. (Boston : Houghton Mifflin, 1978)
Seemingly a girl who has everything, Natalie, at seventeen, goes in pursuit of her real mother.
Booklist.
Wilson's Junior High School.
5.5
7-10.
Young Adult
Keywords: Adoption -- Fiction; Mothers and daughters -- Fiction; Adoption -- Fiction; Family life -- Fiction; Mother-daughter relationship -- Fiction